Spontaneous infarction in fibroadenoma of breast: a rare pathological finding in a common pathological entity - Agarwal, Puneet; Badkur, Mayank; Dausage, Chirag (International Surgery Journal, 2018)
Fibroadenoma is one of the most prevalent benign tumour in adolescent women. It accounts for 20% of all benign breast tumours. Spontaneous infarction in fibroadenoma is very unwonted and mostly, it is associated with gravidity or lactation. Infarction can additionally occur as a complication of antecedent fine-needle aspiration biopsy. At the institution during 2-years period we incidentally found three such cases of spontaneous infarction of fibroadenoma over varied age groups which surprised us. So, reviewed the literature and presented our findings. Three fibroadenomas with features of central necrosis were diagnosed on excision and biopsy. Spontaneous infarction within fibroadenoma is a rare occurrence. It causes diagnostic difficulties, hence conscientious search and possibility of this entity should be must during the evaluation of breast lump.